Neutrophil Extracellular Traps Effectively Control Acute Chikungunya Virus Infection - Hiroki, Carlos H.; Toller-Kawahisa, Juliana E.; Fumagalli, Marcilio J.; Colon, David F.; Figueiredo, Luiz T. M.; Fonseca, Bendito A. L. D.; Franca, Rafael F. O.; Cunha, Fernando Q. (Frontiers in Immunology, 2020)
The Chikungunya virus (CHIKV) is a re-emerging arbovirus, in which its infection causes a febrile illness also commonly associated with severe joint pain and myalgia. Although the immune response to CHIKV has been studied, a better understanding of the virus-host interaction mechanisms may lead to more effective therapeutic interventions. In this context, neutrophil extracellular traps (NETs) have been described as a key mediator involved in the control of many pathogens, including several bacteria and viruses, but no reports of this important protective mechanism were documented during CHIKV infection. Here we demonstrate that the experimental infection of mouse-isolated neutrophils with CHIKV resulted in NETosis (NETs release) through a mechanism dependent on TLR7 activation and reactive oxygen species generation. In vitro, mouse-isolated neutrophils stimulated with phorbol 12-myristate 13-acetate release NETs that once incubated with CHIKV, resulting in further virus capture and neutralization. In vivo, NETs inhibition by the treatment of the mice with DNase resulted in the enhanced susceptibility of IFNAR−/− mice to CHIKV experimental acute infection. Lastly, by accessing the levels of MPO-DNA complex on the acutely CHIKV-infected patients, we found a correlation between the levels of NETs and the viral load in the blood, suggesting that NETs are also released in natural human infection cases. Altogether our findings characterize NETosis as a contributing natural process to control CHIKV acute infection, presenting an antiviral effect that helps to control systemic virus levels.